Analysis of the Effect of Self-Control and Financial Attitude on Students’ Financial Management Behavior - Mochammad Teddy Adhytama; Tika Septiani (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
This study aimed to analyze the effect of self-control and financial attitude on students’ financial management behavior in the digital era. The research applied a quantitative approach using a survey method with 120 undergraduate students in Indonesia as respondents. Data were collected through structured questionnaires and analyzed using multiple linear regression. The findings indicated that self-control and financial attitude had a positive and significant effect on financial management behavior, both partially and simultaneously. Self-control emerged as the more dominant factor in influencing students’ ability to manage their finances, particularly in controlling impulsive spending behavior. The model explained 45.2% of the variance in financial management behavior, while the remaining 54.8% was influenced by other variables not examined in this study. These results highlighted the importance of psychological factors in shaping responsible financial behavior among students. The study suggested that improving self-control and fostering a positive financial attitude were essential in promoting better financial management practices, especially in an environment with easy access to digital financial services.